Criminologists on terrorism and homeland security - Forst, Brian; Greene, Jack R.; Lynch, James P. (James Patrick), 1949-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"This volume presents 19 original essays addressing what is widely regarded as the most serious problem confronting America today and for years to come - terrorism - from the unique perspective of criminology. The chapters collected here address such issues as the prevention of terrorism, the applicability of community policing and routine activities models of crime to the problem of terrorism, how to balance liberty and security, and how to think about and manage the fear of terrorism, as well as the coordination of federal and local efforts to prevent and counter terrorism. Criminologists on Terrorism and Homeland Security will be of interest to anyone concerned about violence prevention in general and terrorism in particular, policing, prosecution, adjudication, sentencing and restorative justice"--
Machine generated contents note: 1. Introduction and overview Brian Forst, Jack R. Greene and James P. Lynch; Part I. Nature of the Problem: 2. Manifestations of aggression: terrorism, crime, and war David Klinger and Charles 'Sid' Heal; 3. The etiology of terrorism: theory, data, and methods Quint Thurman and Wayman Mullins; 4. An ecological perspective of terrorism Bryan Vila and Joanne Savage; 5. Gangs and terrorist cells David Curry; 6. Women, crime, and terrorism Rita Simon and Adrienne Tranel; Part II. Strategies for Intervention: 7. Crime prevention strategies and terrorism Cynthia Lum and Christopher Koper; 8. Routine activities theory and the prevention of terrorism James P. Lynch; 9. Soldiers and spies, police and detectives Tomas Mijares and Jay Jamieson; 10. Community policing and homeland security Jack R. Greene; 11. Go analyze! (Connecting the dots) Jean-Paul Brodeur; 12. Managing the fear of terrorism Brian Forst; 13. Should profiling be used to prevent terrorism? A. Daktari Alexander; 14. Federal and local coordination in homeland security Ed Maguire and William King; 15. Liberty and security in an era of terrorism John Kleinig; 16. Regulating terrorism John Braithwaite; Part III. Thinking About Tomorrow: 17. Countering myths about terrorism: some lessons learned from the global terrorism database Gary LaFree; 18. Criminal justice and terrorism: a research agenda Brian Forst.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Terrorism; Terrorism -- Prevention; Internal security; National security; Electronic books